AN INVESTIGATION INTO THE INFLUENCE OF MOTHER TONGUE ON ENGLISH-SPEAKING SKILLS OF STUDENTS IN UFLS - UD - Văn Thị Ánh Hồng (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study aims to investigate the influence of mother tongue on English-speaking skills of second year English majoring students in University of Foreign Language Studies – The University of Danang. The study will find out the problems related to mother tongue influence and propose some effective measures for students to overcome this situation. The data from classroom observation was used to analyze the influence of mother tongue on students’ speaking skills. The findings show that mother tongue really has significant influences on the speaking skills, especially pronunciation of students. Ending sounds and intonation are two aspects that are mostly affected.